(untitled) (Journal of Forensic Medicine & Toxicology, 2019)
Medical Negligence has become more relevant in current scenario because of more numbers of litigations day by day against health service providers. Amount of compensation awarded by honourable court also getting bigger as income and awareness of subject getting treatment also increasing. Proper consent and documentation are important pillars of defence against medical negligence litigation. After inclusion of medical service in COPRA Act compliant against doctors in various consumer forum of court increased significantly. Honourable Supreme Court of India has given various landmark judgements which have significant impact on medical practise and on proceedings of negligence litigation, such as no criminal proceeding against doctor on complain of medical negligence unless there is opinion from independent medical expert and to keep saving life of patient on top most priority and legal duty should be discharged once patient life become sustainable. Various sections of Indian Penal Code are there with punishment if criminal medical negligence proved. In this publication we will discuss various Supreme Court judgements along with relevant sections in relation to Medical Negligence.